African Ancestry, APOL1, candidate genes, CDKN2A/CDKN2B, HDAC9, small vessel disease, stroke, West Africa (2017)
Objective: Worldwide, the highest frequencies of APOL1-associated kidney variants are found in indigenous West Africans among whom small vessel disease (SVD) is chemic stroke is the most common stroke phenotype. The objective of this study was to investigate the association and effect sizes of 23 selected SNPs in 14 genes of relevance, including the APOL1 G1 variants, with the occurrence of SVD ischemic stroke among indigenous West African participants in the Stroke Investigative Research and Education Network (SIREN) Study. Materials and Methods: Cases were consecutively recruited consenting adults (aged 18 years or older) with neuroimaging—confirmed first clinical stroke. Stroke-free controls were ascertained using a locally validated version of the Questionnaire for Verifying Stroke-Free Status (QVSFS). Logistic regression models adjusting for known vascular risk factors were fitted to assess the associations of the 23 SNPs in rigorously phenotyped cases (N = 154) of SVD ischemic stroke and stroke-free (N = 483) controls. Results: Apolipoprotein L1 (APOL1) rs73885319 (OR = 1.52; CI: 1.09-2.13, P value = .013), rs2383207 in CDKN2A/CDKN2B (OR = 3.08; CI: 1.15-8.26, P – value = .026) and rs2107595 (OR = 1.70; CI: 1.12-2.60, P-value = .014) and rs28688791 (OR = 1.52; CI: 1.03-2.26, P-value = .036) in HDAC9 gene were associated with SVD stroke at 0.05 significance level. Polymorphisms in other genes did not show significant associations. Conclusion: This is the first report of a specific association of APOL1 with a stroke subtype. Further research is needed to confirm these initial findings and deepen understanding of the genetics of stroke in people of African ancestry with possible implications for other ancestries as all humans originated from Africa